1994
DOI: 10.1042/bj2990587
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the secondary structure of selected melittin analogues with different haemolytic activities

Abstract: In earlier studies, we have reported that minor modifications in the amino acid sequence of melittin result in dramatic changes in its biological activity. In the current study, we have investigated the secondary structure of melittin analogues with either increased or decreased haemolytic activity in order to further our understanding of the structural features involved in the binding and/or insertion of peptides into a phospholipid membrane from solution. This was accomplished by analysing the c.d. spectra o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…For example, substitution of lysine in the hydrophobic N-terminal part of melittin decreases the hydrophobic moment of the peptide and results in the loss of both antimicrobial and hemolytic activity. 107 Cytotoxicity studies of magainin and PGLa analogue peptides produce similar results. 108 In addition to whole cell studies, the loss of antibacterial selectivity due to enhanced amphipathicity was confirmed in lipid model systems where the increase in the permeabilizing efficiency of the peptides is more pronounced in their interaction with neutral phospholipid vesicles.…”
Section: Determinants Of Linear Amp-lipid Bilayer Interactionssupporting
confidence: 68%
“…For example, substitution of lysine in the hydrophobic N-terminal part of melittin decreases the hydrophobic moment of the peptide and results in the loss of both antimicrobial and hemolytic activity. 107 Cytotoxicity studies of magainin and PGLa analogue peptides produce similar results. 108 In addition to whole cell studies, the loss of antibacterial selectivity due to enhanced amphipathicity was confirmed in lipid model systems where the increase in the permeabilizing efficiency of the peptides is more pronounced in their interaction with neutral phospholipid vesicles.…”
Section: Determinants Of Linear Amp-lipid Bilayer Interactionssupporting
confidence: 68%
“…Mel.subK7I is an analog with a single Lys-to-Ile substitution at position 7 ( Table 1) that results in reduced interaction with membranes and reduced toxicity to red blood cells, as measured by its hemolytic properties (22). Surprisingly, mel.subK7I initiated P. digitatum permeabilization at concentrations very similar to those of PAF26 and melittin (0.5 to 1 M) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5D). At the micromolar concentrations of peptides used in these studies, both melittin and subK7I showed a random coil conformation in the absence of TMV RNA (15). As shown in Fig.…”
Section: Methodsmentioning
confidence: 80%
“…5D, in the presence of TMV RNA melittin folded into an a-helical conformation, while subK7I adopted a distorted ,3-sheet. As mentioned above, such variations in folding may be related to the differences observed between the antiviral activities of melittin and subK7I, as seen in earlier structure-activity relationship studies with melittin derivatives (15,16).…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation